BIBLIOTECARUL UNIVERSITAR – MEDIATOR ÎN PROCESUL DE STUDIERE ŞI CERCETARE - HABAŞESCU, şef serviciu, Biblioteca Ştiinţifică, ASEM, Silvia (BIBLIOPOLIS, 2020)
The author presents some aspects of collaboration established between ASEM and universities from Norway and Romania. Especially effective proved to be the projects aimed at: developing new information services in economic education and information literacy, sociological research for the users of the ASEM Scientific Library (students, master and PhD).